Broiler recycled litter treatments against Clostridium perfringens and enterobacteria in conventional and dark house systems - Benedet, João Paulo; Perosa, Fernanda Felicetti; Silva, Isabela Gimenes da; Troncarelli, Marcella Zampoli; Rauber, Ricardo Hummes; Gomes, Teane Milagres Augusto (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the effectiveness of quicklime and shallow fermentation applications on the reduction of Clostridium perfringens and enterobacteria in recycled poultry litter, in dark house and conventional systems. Eighty litter samples were evaluated, being divided into four groups: litter treated with quicklime in dark house; litter treated with shallow fermentation and quicklime in dark house; and litter treated with quicklime in conventional broiler house; litter treated with shallow fermentation and quicklime in conventional broiler house. Samples were collected one day before slaughter and five days after litter treatment and were subjected to the quantitative microbiological analysis of enterobacteria and C. perfringens. The bacterial load in pre-treated litter was similar between the dark house and conventional systems. The groups treated only with quicklime showed a significant reduction of enterobacteria in both systems. The reduction of C. perfringens was only observed in the litter group treated with shallow fermentation and quicklime, in conventional broiler house. The use of 500 g m-² quicklime is the most effective method to reduce enterobacteria load in broiler litter both in the dark house and conventional broiler house systems. The combined treatment of shallow fermentation for seven days with the subsequent application of 500 g m-² quicklime is efficient for the reduction of C. perfringens in broiler litter, in conventional broiler house.